Gothic Experiences in Jane Eyre, Wuthering Heights, and The Tenant of Wildfell Hall - Tine, Etienne Pathe (European Scientific Journal, ESJ, 2024)
This paper thoroughly analyses the theme of the gothic imagination in the works of Charlotte, Emily, and Anne Bronte, specifically in Jane Eyre, Wuthering Heights, and The Tenant of Wildfell Hall. The novels portray romantic and sublime scenes with elements of terror, horror, and the uncanny, which intensify the expression of the gothic feelings experienced by the characters. The study also explores women’s suffering in the context of gothic thought. Various factors inherent to the gothic genre contribute to the 19th-century readers’ fascination with the supernatural and thrilling emotions. This work explores gothic experiences depicted in novels using gothic tropes and critical approaches such as Marxism, feminism, or psychoanalysis. The use of the framing narrative technique remains a distinctive aspect of this study which worthily includes The Tenant of Wildfell Hall, a book that many critics have wrongly overlooked when interpreting the Bronte sisters’ novels in the light of the gothic trend. The analysis considers the common gothic features that characterize the novels, rather than treating them separately. This reinforces and enhances the scope of the analysis of the Gothic vision of these Victorian novelists.